Rectal carcinoid tumor with bone marrow and osteoblastic bone metastasis: A case report - Metin ÖZKAN,; Özlem ER,; İ. Ökkeş KARAHAN,; Kemal DENİZ,; Ramazan COŞKUN,; Can KÜÇÜK,; Alper YURCİ,; Mustafa ALTINBAŞ, (Turkish Journal of Gastroenterology, 2019)
-